(untitled) (The Voz a Vos Bulletin, 2024)
The need for a profound transformation in pedagogical practices to achieve a truly inclusive education is explored. It is emphasized that inclusion goes beyond the mere physical integration of students with disabilities or differences in the classroom. True inclusion implies a commitment to equity, social justice, and the appreciation of diversity in all its manifestations. A key aspect is the importance of critical pedagogy as a tool to question and transform traditional educational structures that perpetuate exclusion. Rather than adapting pedagogical methods after integration, it is proposed that inclusion should be integrated into pedagogical design from the beginning, to ensure that all students, regardless of their differences, have equal access to education. The need to restructure curricular content to reflect and value the diverse experiences, knowledge, and cultures of students is underlined. This approach must be intersectional, considering how factors such as race, gender, class, and disability interact and affect the educational experience of each student. Another key point is the importance of the active participation of students in their learning process. Listening to and valuing the voices of those students who have been historically marginalized is essential to building an inclusive education that responds to their needs and perspectives. Finally, although the implementation of inclusive education faces significant challenges, including institutional and cultural resistance, the need to persist in the fight for a more just education is highlighted. Redefining the concept of inclusion in the educational system is essential to creating an environment where diversity is celebrated and all students can fully participate in their education.